Multi-Stakeholder Collaboration in the Development of Tourism Villages in Garut Regency: Collaborative Governance Approach - Meliana, Mila; Geusan Akbar, Gugun; Kania, Ikeu (Jurnal Toursci, 2025)
Background. Garut Regency has more than 20 villages that have been developed into tourist villages with various concepts, such as tourism-based tourism villages, nature tourism, and agrotourism. This uniqueness gives villages in Garut great potential to be developed into tourism villages based on local culture and traditions. The development of tourist villages in Garut is expected to introduce tourists to natural and cultural wealth and become the driving force of the village community's economy through the tourism sector. Aims. This study aims to analyze the application of Collaborative Governance in developing tourist villages in Garut Regency. Methods. This study uses a qualitative approach to analyze multi-stakeholder collaboration in the development of tourism villages in Garut Regency using the Collaborative Governance framework. Data was collected through in-depth interviews, Focus Group Discussions (FGDs), and participatory observations to understand the dynamics and challenges of collaboration between governments, business actors, and communities. Result. The data results were analyzed thematically and content-wise to explore themes related to communication, coordination, and obstacles in collaboration that support the development of tourism villages. The study's results show that although there has been progress in implementing Collaborative Governance, there are still challenges in terms of coordination between actors and fulfilling the community's capacity to play an active role. Conclusion. This study suggests the need to strengthen community participation, increase human resource capacity, and establish a more structured collaboration mechanism to support the sustainable development of tourism villages in Garut Regency. Implementation. These findings are expected to provide insight for policymakers in formulating more effective collaboration-based tourism village development strategies.